2015
DOI: 10.1534/g3.115.019091
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen forSaccharomyces cerevisiaeMutants That Fail to Enter Quiescence

Abstract: Budding yeast begin the transition to quiescence by prolonging G1 and accumulating limited nutrients. They undergo asymmetric cell divisions, slow cellular expansion, acquire significant stress tolerance and construct elaborate cell walls. These morphologic changes give rise to quiescent (Q) cells, which can be distinguished from three other cell types in a stationary phase culture by flow cytometry. We have used flow cytometry to screen for genes that are required to obtain the quiescent cell fraction. We fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…To test this, we first purified quiescent yeast from 3-day saturated cultures using a Percoll gradient. As previously observed, quiescent yeast required longer treatment with an increased amount of Zymolyase to compensate for a highly-fortified cell wall (LI et al 2015). We observed that the rapid protocol with an extended Zymolyase incubation can efficiently and reproducibly recover nucleosome footprints (Figure 2A).…”
Section: Streamlined Protocol For Rapid Recovery Of Nucleosome Footprsupporting
confidence: 80%
“…To test this, we first purified quiescent yeast from 3-day saturated cultures using a Percoll gradient. As previously observed, quiescent yeast required longer treatment with an increased amount of Zymolyase to compensate for a highly-fortified cell wall (LI et al 2015). We observed that the rapid protocol with an extended Zymolyase incubation can efficiently and reproducibly recover nucleosome footprints (Figure 2A).…”
Section: Streamlined Protocol For Rapid Recovery Of Nucleosome Footprsupporting
confidence: 80%
“…To test this hypothesis, we screened a number of chromatin remodeling mutants in an auxotrophic background for defects in Q entry, and discovered that the SWI/SNF complex was the strongest hit. In support of these results, the Snf6 subunit of the SWI/SNF complex was shown to be required for Q cell formation (Li et al, 2015), and Snf2 was predicted to be a quiescence specific transcription factor by computational analyses (Reimand et al, 2012). Additionally, the SWI/SNF complex is a well-established regulator of transcription, known for activating glucose-repressed genes (Abrams et al, 1986) and genes involved in metabolic regulation and/or stress through its nucleosome remodeling activity (Awad et al, 2017;CĆ“tĆ© et al, 1994;Dutta et al, 2014;Erkina et al, 2008;Geng and Laurent, 2004;Peterson et al, 1994;Qiu et al, 2016;Shivaswamy and Iyer, 2008;Wang et al, 2018).…”
Section: Snf2 Is Required For Q Entrymentioning
confidence: 64%
“…The requirement for Snf2 during Q entry is strongest just before the DS As mentioned above, the process of Q entry begins even before glucose has been depleted from the media, and lasts nearly a week (Allen et al, 2006;Li et al, 2015). Snf2 could be involved in regulating any or even multiple stages of the process.…”
Section: Snf2 Is Required For Q Entrymentioning
confidence: 98%
“…Among AFB 1 resistant genes were those involved in protein degradation and ammonia transport, actin reorganization, tRNA modifications, ribosome biogenesis and RNA translation. Some genes encoding these functions, such as BIT2 and TRM9, have important roles in maintaining genetic stability and in doublestrand break repair (Begley, et al, 2007;Schmidt et al, 1996;Schonbrun et al, 2012;Shimada et al, 2013).Several genes, such as PPG1, are involved in glycogen accumulation; these genes are also required to enter the quiescent state (Li et al, 2015). Other genes are involved in cell wall synthesis, including MNN10, SCW10 and ROT2; we speculate that cell wall synthesis genes confer resistance by impeding AFB 1 entrance into the cell, while genes involved in protein degradation in the ER may stabilize CYP1A2 and thus enhance AFB 1 -conferred genotoxicity (Murray and Sa-Correia, 2001).…”
Section: Discussionmentioning
confidence: 99%